2022
DOI: 10.1155/2022/6650763
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of the Efficacy and Safety of Shuxuening Injection in the Treatment of Unstable Angina

Abstract: The aim of this study was to systematically review the efficacy and safety of Shuxuening injection combined with conventional Western medicine in the treatment of unstable angina. Randomized controlled trials of Shuxuening injection combined with conventional Western medicine in the treatment of unstable angina were searched by the computer system from PubMed, EMBASE, Cochrane Library, VIP, CNKI, Wanfang Database, and Chinese Biomedical Database since the establishment of the database until June 2020, accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…[14,15] SXN is a Chinese patent medicine processed from Ginkgo biloba extract, which has the effect of promoting blood circulation. [21,31] However, there is still a lack of strong evidence on the efficacy and safety of ERI combined with SXN in the treatment of acute cerebral infarction. The results of this study show that ERI combined with SXN can improve the curative effect, improve brain nerve function damage and hemorheology, and reduce the expression level of inflammatory factors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[14,15] SXN is a Chinese patent medicine processed from Ginkgo biloba extract, which has the effect of promoting blood circulation. [21,31] However, there is still a lack of strong evidence on the efficacy and safety of ERI combined with SXN in the treatment of acute cerebral infarction. The results of this study show that ERI combined with SXN can improve the curative effect, improve brain nerve function damage and hemorheology, and reduce the expression level of inflammatory factors.…”
Section: Discussionmentioning
confidence: 99%
“…[14,15] SXN is a Chinese patent medicine processed from Ginkgo biloba extract, which has the effect of promoting blood circulation. [21,31] However, there is still a lack of strong evidence on the efficacy and safety of ERI combined with SXN in the treatment of acute cerebral infarction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the wide application of SXNI and the growing number of clinical studies, the number of systematic reviews (SRs) assessing its effectiveness and safety has also increased (Zhou et al, 2015;Wu et al, 2017;Fan et al, 2022). However, an umbrella review of these SRs has identified several shortcomings.…”
mentioning
confidence: 99%